Zero-hours contracts in a frictional labor market - Juan J. Dolado; Etienne Lalé; Hélène Turon (Université du Québec à Montréal, École des sciences de la gestion (ESG UQAM), Département des sciences économiques, 2022)
We propose a model to evaluate the U.K.'s zero-hours contract (ZHC) - a contract that exempts employers from the requirement to provide any minimum working hours, and allows workers to decline any workload. We find quantitatively mixed welfare effects of ZHCs. On one hand they unlock job creation among firms that face highly volatile business conditions and increase labor force participation of individuals who prefer flexible work schedules. On the other hand, the use of ZHCs by less volatile firms, where jobs are otherwise viable under regular contracts, reduces welfare and likely explains negative employee reactions to this contract.
Keywords: E24; J22; J23; J63; L84; 330; Zero-hours contracts; Working hours; Gig economy; Flexibility